From pastures to forests: Changes in Mediterranean wild bee communities after rural land abandonment. Issue 3 (5th January 2022) - Penado, Andreia; Rebelo, Hugo; Goulson, Dave; Wood, Thomas J.; Porto, Miguel; Rotheray, Ellen L.; Beja, Pedro
Abstract: In farmland landscapes worldwide, there are pervasive trends for either intensification or abandonment. Intensification is a widely recognised driver of wild bee declines, but little is known about the consequences of land abandonment, though it involves major habitat shifts from fallows, pastures and meadows, to shrublands and forests. Focusing on a Mediterranean landscape, we investigated long‐term changes in wild bee communities during secondary vegetation succession after land abandonment. We used a space‐for‐time substitution approach, sampling plants and wild bees on five successional stages, from grasslands, through shrublands, to oak woodlands. We recorded 2721 bees, representing over 150 species. Grasslands had the highest wild bee abundance and high diversity of oligolectic species. Moving through successional stages, there was a rapid decline in bee abundance combined with a progressive accumulation of rare species, resulting in maximum diversity of the overall community, ground nesters, polyleges, and oligoleges in oak woodlands. Bee diversity was positively related to plant taxonomic and phylogenetic diversity. There was high turnover in community composition along the succession, with species occurring in grasslands being largely absent from later successional stages, and vice versa. From 21 indicator species, 17 were associated with grasslands, including the only threatened species. Our results suggest that a mosaic of habitats at different successional stages, particularly grasslands and oak woodlands, are necessary to maximise the diversity and abundance of wild bees at the landscape scale. Sustained management is thus needed under land abandonment to retain early‐successional herbaceous habitats and to ensure woodland regeneration and protection. Abstract : Land abandonment causes the progressive replacement of pastures, meadows and other early‐successional habitats by shrublands and woodlands, but its effects on pollinators such as wild bees are poorly unknown. Wild bee abundance was highest in grasslands, while maximum bee diversity was reached in woodlands due to accumulation of rare species during succession. There was high species turnover along the successional gradient. Conserving Mediterranean wild bees requires landscape mosaics of successional vegetation stages, which imply preventing shrub encroachment of early‐successional herbaceous habitats and promoting the restoration and protection of native woodlands.